Lectotypification of the name Polymnia maculata Cav. (Asteraceae: Millerieae) - Vitali, Maira Soledad (2015)
The typification of the name Polymnia maculata Cav. is discussed and the illustration made by Cavanilles in 1795 is designated as the lectotype and the specimen MA 606169 is designated as epitype.